Relationship Of Eating Frequency And Dietary Patterns With BMI Among Culinary Students At Universitas Negeri Jakarta - Ambar Maariyah Septianingsih; Rusilanti Rusilanti; Nur Riska (Community Engagement and Emergence Journal (CEEJ), 2026)
Background: University students’ eating frequency and dietary patterns remain varied and do not fully comply with balanced nutrition guidelines, potentially increasing the risk of nutritional problems. Objective: To analyze the relationship between eating frequency, dietary patterns, and Body Mass Index (BMI) among Culinary students at Universitas negeri Jakarta. Methods: This quantitative correlational study used a cross-sectional design involving 147 students selected through proportionate stratified random sampling. Eating frequency was assessed using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), while dietary patterns were measured using Food Recall. Data were analyzed using Spearman’s rank correlation and ordinal logistic regression. Results: No significant relationship was found between the frequency of energy (p=0.125), protein (p=0.140), and fat intake (p=0.516) and BMI. However, carbohydrate intake frequency was significantly associated with BMI (p=0.004). Dietary patterns of energy (p=0.001), carbohydrate (p=0.036), protein (p=0.001), and fat intake (p=0.026) were significantly associated with BMI. Carbohydrate intake pattern was identified as the strongest determinant, increasing the likelihood of BMI variation by 2.94 times. Conclusion: Carbohydrate intake frequency and dietary patterns of energy, carbohydrate, protein, and fat were significantly associated with BMI. Recommendation: Nutrition education programs on healthy eating frequency and dietary patterns should be strengthened among university students.